Scalable block preconditioners for saturated thermo-hydro-mechanics problems - Ana C. Ordonez; Nicolas Tardieu; Carola Kruse; Daniel Ruiz; Sylvie Granet (Advanced Modeling and Simulation in Engineering Sciences, 2023)
Abstract We are interested in the modelling of saturated thermo-hydro-mechanical (THM) problems that describe the behaviour of a soil in which a weakly compressible fluid evolves. It is used for the evaluation of the THM impact of high-level activity radioactive waste exothermicity within a deep geological disposal facility. We shall present the definition of a block preconditioner with nested Krylov solvers for the fully coupled THM equations. Numerical results reflect the good performance of the proposed preconditioners that show to be weakly scalable until more than 2000 cores and more than 1 billion degrees of freedom. Thanks to their performance and robustness, a real waste storage problem on a scale, to our knowledge, unprecedented in the field, can be addressed.